CLINICAL PROFILE OF PATIENTS WITH UNDESCENDED TESTIS IN TERTIARY HOSPITAL - Sulistyanti, Rachma Fitri; Daryanto, Besut; Nurhadi, Pradana (Indonesian Urological Association, 2025)
Objective: The objective of this study is to present the clinical profile of patients with UDT in tertiary hospital. Material & Methods: This study used a descriptive retrospective approached with approved ethical number 400/019/K.3/102.7/2024. Collecting identification was done by tracing UDT case-patient documents from January 2015 to December 2023. The characteristics observed were age, location of UDT, unpalpable or palpable, patient's address, and antenatal care examination. Results: From 107 UDT patients, 16 patients (24.31%) was diagnosed at the age 19 until 24 months old and decreased in puberty ages. 74 cases of UDT (69.16%) are unilateral UDT with almost the same distribution between left and right. In 75 cases of unpalpable UDT (70.09%), it was found that the testis were still viable in 57 cases during diagnostic laparoscopic. On average, there are 63 patients (58.87%) coming from the Malang area. The average number of patients receiving antenatal care from midwives is 61 cases (62.61%). Conclusion: In all, many cases of UDT under 12 years old were found, with the majority is Unpalpable Unilateral UDT, patient come from the Malang area and have received antenatal care from midwives. The data obtained can be used as a database for enhancing the standard of care. Keywords : Clinical profile, UDT, Malang